Nebenwirkungen oraler Therapien in der gynäkologischen Onkologie - Pöschke, Patrik; Beckmann, Matthias; Gaß, Paul (Tägliche Praxis, 2021)
Oral targeted therapies have great potential in gynecological oncology. Both inhibitors of cyclin-dependent kinases 4 and 6 (CDK4/6) like Ribociclib, Palbociclib or Abemaciclib and poly(ADP-ribose) polymerase (PARP) inhibitors like Olaparib, Niraparib, Rucaparib or Talazoparib have become standard of therapy as mono- and combination therapy for women suffering from breast or ovarian cancer. Regular therapy monitoring as well as supportive interventions lead to a low rate of serious side effects and adverse reaction-related discontinuations of therapy. Most common side effects in most oral therapies are neutropenia between 7 and 53 % of grade 3 and 4 toxicities, anemia between 3 and 39 % of grade 3 and 4 toxicities, and nausea between 32 and 77 % for all grades of toxicities. Those are the most common among a wide range of possible adverse events, which are in most cases very controllable, resulting from common signaling pathways involved in homeostatic function and regeneration of mucosal cells throughout the body and malignant cell development. Dose reductions are possible in all of these therapies. These therapies are also reflected in the partly better quality of life and significant longer time to deterioration than in comparative therapies with improved progression-free, and in some cases also shown overall survival compared to the previous therapy standard. Since September 2020, another new substance of oral therapeutics has been approved in Germany, Alpelisib, a PIK3CA inhibitor. The aim of this work is to provide an overview of the new therapeutics, their most frequent side effects and the associated management to increase therapy adherence and therefore quality of life and therapy results.
CRIS-Team Scopus Importer:2024-12-16
Keywords: BRCA; breast cancer; CDK4/6; oral therapy; ovarian cancer; PARP; PIK3CA